Endovascular Therapy for Acute Stroke with a Large Ischemic Region - Shinichi Yoshimura; Nobuyuki Sakai; Hiroshi Yamagami; Kazutaka Uchida; M. Beppu; Ḱazunori Toyoda; Yuji Matsumaru; Yasushi Matsumoto; Kazumi Kimura; Masataka Takeuchi; Yukako Yazawa; Naoto Kimura; et al. (2022)
Endovascular therapy for acute ischemic stroke is generally avoided when the infarction is large, but the effect of endovascular therapy with medical care as compared with medical care alone for large strokes has not been well studied.